Piezoelectric Nanogenerator Based on In Situ Growth All‐Inorganic CsPbBr3 Perovskite Nanocrystals in PVDF Fibers with Long‐Term Stability. (19th March 2021) - Chen, Huiying; Zhou, Linlin; Fang, Zhi; Wang, Shuize; Yang, Tao; Zhu, Laipan; Hou, Xinmei; Wang, Hailong; Wang, Zhong Lin
Abstract: Inorganic lead halide perovskite has become an emerging material for modern photoelectric and electronic nanodevices due to its excellent optical and electronic properties. In view of its huge dielectric and electrical properties, inorganic CsPbBr3 perovskite is introduced into the piezoelectric nanogenerator (PENG). Based on one‐step electrospinning of solutions containing CsPbBr3 precursors and polyvinylidene difluoride (PVDF), in situ growth of CsPbBr3 nanocrystals in PVDF fibers (CsPbBr3 @PVDF composite fibers) with highly uniform size and spatial distribution are synthesized. The CsPbBr3 @PVDF composite fibers based PENG reveals an open‐circuit voltage ( V oc ) of 103 V and a density of short‐circuit current ( I sc ) of 170 µ A cm −2, where the V oc is comparable to the state‐of‐the‐art hybrid composite piezoelectric nanogenerators (PENGs) and the density of I sc is 4.86 times higher than that of lead halide perovskites counterpart ever reported. Moreover, CsPbBr3 @PVDF composite fibers based PENG exhibits fundamentally improved thermal/water/acid–base stabilities. This study suggests that the CsPbBr3 @PVDF composite fiber is a good candidate for fabricating high‐performance PENGs, promising application potentials in mechanical energy harvesting and motion sensing technologies. Abstract : A high‐performance piezoelectric nanogenerator (PENG) based on the composite fibers combined polyvinylidene difluoride (PVDF) with CsPbBr3 nanocrystals is constructed by in situ growth method. The PENG reveals a density of short‐circuit current ( I sc ) of 170 µA cm −2, which is 4.86 times higher than that of lead halide perovskites counterpart ever reported. Moreover, the PENG exhibits fundamentally improved thermal/water/acid‐base stabilities.